2009
DOI: 10.1021/ja808881x
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting Substituent Effects for the Synthesis of a Photooxidatively Resistant Heptacene Derivative

Abstract: Substituent effects have been exploited to produce an unusually persistent heptacene derivative. In total, four new heptacene derivatives with varying levels of photooxidative resistance (1 < 2 < 3 < 4) have been synthesized. A combination of p-(t-butyl)thiophenyl substituents at positions 7 and 16 (i.e., arylthio substituents attached to the most reactive ring) and o-dimethylphenyl substituents at positions 5, 9, 14, and 18 (i.e., steric resistance on neighboring rings) make heptacene derivative 4 especially … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
101
0
9

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(117 citation statements)
references
References 16 publications
3
101
0
9
Order By: Relevance
“…Two more aryl substituted heptacenes (53 and 54) were prepared and investigated by the Miller group in 2009 (Fig. 26) [58]. Beyond Pentacenes: Synthesis and Properties of Higher Acenes 19 As expected, the 7,16-di(p-tert-butylphenyl)heptacene 53 decomposed rapidly in solution in an ambient atmosphere in the presence of light, while the four additional o,o-dimethylphenyl substituents in 54 enhance the stability somewhat [58].…”
Section: Aryl Substituted Heptacenesmentioning
confidence: 93%
“…Two more aryl substituted heptacenes (53 and 54) were prepared and investigated by the Miller group in 2009 (Fig. 26) [58]. Beyond Pentacenes: Synthesis and Properties of Higher Acenes 19 As expected, the 7,16-di(p-tert-butylphenyl)heptacene 53 decomposed rapidly in solution in an ambient atmosphere in the presence of light, while the four additional o,o-dimethylphenyl substituents in 54 enhance the stability somewhat [58].…”
Section: Aryl Substituted Heptacenesmentioning
confidence: 93%
“…Though the polyacene molecules are reactive, their derivatives seem to be more stable [17][18][19]. Payne et al [17], Chun et al [18], and Kaur et al [19] have reported the synthesis of heptacene derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…Payne et al [17], Chun et al [18], and Kaur et al [19] have reported the synthesis of heptacene derivatives. Weisman et al [20] have reported a theoretical and spectroscopic study of dibenzopolyacene molecules up to the dibenzo[jk,a1b1]octacene range.…”
Section: Introductionmentioning
confidence: 99%
“…Recent work has shown that bulky substituents kinetically stabilize the heptacene framework, thus providing interesting compounds for materials applications. [13][14][15] Clars discouraging statement surely refers to experiments under conventional conditions at room temperature. By using cryogenic matrix-isolation techniques, we have defied Clars prediction and herein report the synthesis of octacene (3) and nonacene (4).…”
mentioning
confidence: 99%